The Power Game in Byzantium : Antonina and the Empress Theodora. - Evans, James Allan (Bloomsbury Publishing, 2011)
This title presents an original portrayal of Justinian's reign, its politics and theological disputes, focusing on the lives of two extraordinary women who wielded power and influence. A fascinating exploration of the corridors of power in Byzantium of the time of Justinian (527-565), the book reveals how Empress Theodora and Antonina, both alumnae of the theatre, were remarkable examples of social mobility, moving into positions of power and influence, becoming wives of key figures. Theodora had three aims: to protect those Christians who would not accept the Chalcedonian Creed; to advance th.